“Ninguna niña o mujer merece pasar por todo esto”: Participación española en la protesta contra los crímenes deepfake en Corea del Sur de 2024 - Rubio-López, Nerea; Muñoz-del-Pino, Iris María (Cuadernos de Documentación Multimedia, 2025)
In an increasingly digitised world, the development of new technologies is unfortunately accompanied by new forms of violence against women. South Korea is a highly developed country in this field, and the number of sex crimes related to deepfakes (images manipulated using artificial intelligence) and their dissemination through messaging channels has increased alarmingly there. The discovery of a Telegram channel with over 220,000 members where deepfakes of hundreds of women, primarily students, were disseminated marked a turning point for Korean women. On 1 September 2024, Korean feminists organised a large protest that took place both in person and online. In response to attempts by the media to downplay the incident, the activists urged feminists worldwide to raise awareness of the situation in South Korea. This article examines Spanish participation in the protest. To this end, tweets using the hashtag #Digital_Sex_Crimes_in_School were analysed. The results show that Spanish feminists considered international solidarity among women to be essential in raising awareness of the deepfake scandal. They also emphasised that just because something does not happen in a particular country does not mean that it cannot happen there, and therefore it should not be considered a foreign problem despite geographical barriers. Finally, they emphasised the importance of collaborating to demand institutional responses to the increasing digital misogyny.